2023
DOI: 10.1021/acs.est.3c01866
|View full text |Cite
|
Sign up to set email alerts
|

Passive-Sampler-Derived PCB and OCP Concentrations in the Waters of the World─First Results from the AQUA-GAPS/MONET Network

Abstract: Persistent organic pollutants (POPs) are recognized as pollutants of global concern, but so far, information on the trends of legacy POPs in the waters of the world has been missing due to logistical, analytical, and financial reasons. Passive samplers have emerged as an attractive alternative to active water sampling methods as they accumulate POPs, represent time-weighted average concentrations, and can easily be shipped and deployed. As part of the AQUA-GAPS/MONET, passive samplers were deployed at 40 globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…This highlights the ecological risk of these pseudopersistent PCMs and other commercial chemicals in the aquatic environment. Finally, the present study indicated that passive sampling techniques performed fairly well in monitoring pseudopersistent organic pollutants in freshwater on a national or a large geographical scale, supporting the logistics of field work for the global network of AQUA-GAPS. , …”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This highlights the ecological risk of these pseudopersistent PCMs and other commercial chemicals in the aquatic environment. Finally, the present study indicated that passive sampling techniques performed fairly well in monitoring pseudopersistent organic pollutants in freshwater on a national or a large geographical scale, supporting the logistics of field work for the global network of AQUA-GAPS. , …”
Section: Resultssupporting
confidence: 72%
“…These provide a great opportunity to evaluate the effects of anthropogenic activities and natural factors on spatial distributions of synthetic musks, shedding some light on ecological risks of commercial chemicals in aquatic environments of a national scale. Passive sampling techniques are able to determine the freely dissolved concentrations of organic contaminants in a large region. , Previous studies have demonstrated that it is feasible to monitor freely dissolved PCMs in a field environment with passive samplers. ,,, Low-density polyethylene (LDPE) membrane was recommended as the sorbent phase to monitor various hydrophobic organic compounds in a global monitoring program [Aquatic Global Passive Sampling (AQUA-GAPS)] due to its outstanding performance and convenience . As part of the AQUA-GAPS, herein, a self-developed passive sampling device with LDPE as the sorbent phase was applied for the first in situ tracking of freely dissolved synthetic musks in lakes and reservoirs across China (latitude: 22° 59′ N to 44° 51′ N), covering the Songhua River Basin and Liaohe River Basin in Northeast China, the Tarim River Basin in Northwest China, lakes in the Tibetan Plateau in Southwest China, the Yangtze River Basin in Mid and East China, and the Pearl River Basin in South China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet beyond the visible signs of a changing Arctic, Indigenous peoples, residents, and newcomers to the Arctic also have to deal with invisible factors impacting health and well-being. The Arctic environment and food are known to be contaminated by a wide range of synthetic organic contaminants, typically via long-range transport from the industrial and urban regions in the temperate regions (North America, Europe and Russia/Asia), including polychlorinated biphenyls (PCBs), per- and polyfluorinated alkyl substances (PFAS), mercury (Hg), lead and emerging contaminants . Several Arctic communities are known to have elevated levels of these contaminants, with known or suspected adverse health impacts .…”
Section: Environmental Impacts In the Arcticmentioning
confidence: 99%
“…Since the 1940s, it has been widely used all over the world because of its strong insecticidal efficacy [1]. OCPs can be divided into two categories: one is chlorobenzene and its derivatives, such as dichlorodiphenyltrichloroethane (DDTs), hexachlorocyclohexane (HCHs) and hexachlorobenzene, and the other is organochlorine pesticides based on cyclopentadiene, including chlordane, heptachlor, endosulfan and so on [2][3][4][5][6][7][8][9]. OCPs have the characteristics of low volatility, stable chemical properties, not easy to decompose, long residue period, insoluble in water, soluble in fat and organic solvents, high persistence, bioaccumulation and biotoxicity [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%